2015
DOI: 10.1080/10286020.2015.1054816
|View full text |Cite
|
Sign up to set email alerts
|

New α-pyrone and phthalide from the Xylariaceae fungus

Abstract: A new α-pyrone xylaripyrone A (1) and a new phthalide xylariphthalide A (2) were isolated from the Xylariaceae fungus (no. 63-19-7-3), along with four related known phthalides (3-6): 4-[(acetyloxy)methyl]-7-methoxy-6-methyl-1(3H)-isobenzofuranone (3), convolvulol (4), 7-methoxy-4,6-dimethyl-3H-isobenzofuran-1-one (5), and convolvulanic acid B (6). Their structures were determined on the basis of IR, MS, and NMR spectroscopic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Among our recent discoveries [11,12,13,14,15,16,17,18,19,20,21], we recently reported that a strain of Streptomyces sp. HK-2006-1 produced both aldgamycins and chalcomycins, which are 16-membered macrolides [11,21].…”
Section: Introductionmentioning
confidence: 99%
“…Among our recent discoveries [11,12,13,14,15,16,17,18,19,20,21], we recently reported that a strain of Streptomyces sp. HK-2006-1 produced both aldgamycins and chalcomycins, which are 16-membered macrolides [11,21].…”
Section: Introductionmentioning
confidence: 99%